2019
DOI: 10.1002/1873-3468.13499
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 and co‐chaperones: a multitaskers’ view on plant hormone biology

Abstract: In order to survive under ever‐changing conditions plants must be able to adaptively respond to their environment. Plant hormones and the signaling cross‐talk among them play a key role in integrating external and internal cues, enabling the plants to acclimate accordingly. HSP90 and several of its co‐chaperones are known as pleiotropic factors involved in the signaling pathways of multiple stress responses, including temperature, drought, and pathogen infection. Recently, hormone receptor components for auxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 139 publications
(248 reference statements)
3
37
0
Order By: Relevance
“…Low‐level induction of HSPs concurrent with induced resistance to Bc , On and Xcv suggests that the same mechanisms that exert abiotic stress tolerance also activate immune mechanisms in tomato, as was previously suggested (di Donato & Geisler, 2019; Yu et al, 2016; Zhang & Sonnewald, 2017). The activation of HSPs by pathogenic processes demonstrates the common signalling pathways that can underlie the plants' response to several different types of stresses, which ideally, would be those manipulated in order to generate resistance and agriculturally desirable cultivars in the face of combinatorial stress created by climate change.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Low‐level induction of HSPs concurrent with induced resistance to Bc , On and Xcv suggests that the same mechanisms that exert abiotic stress tolerance also activate immune mechanisms in tomato, as was previously suggested (di Donato & Geisler, 2019; Yu et al, 2016; Zhang & Sonnewald, 2017). The activation of HSPs by pathogenic processes demonstrates the common signalling pathways that can underlie the plants' response to several different types of stresses, which ideally, would be those manipulated in order to generate resistance and agriculturally desirable cultivars in the face of combinatorial stress created by climate change.…”
Section: Discussionsupporting
confidence: 64%
“…Evidences of commonalities between heat stress and biotic stress signalling pathways have been previously reported (Jacob, Hirt, & Bendahmane, 2017; Suzuki & Katano, 2018; Zhang & Sonnewald, 2017). In particular, HSPs have been demonstrated to be involved in the response to both heat and biotic stressors (di Donato & Geisler, 2019; Yu et al, 2016). Overexpression of HSPs in plants has been proposed as one of the potential strategies to combat heat stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, chaperones are considered as powerful buffers against protein misfolding during environmental stress (including drought) and consequent genetic variations (Carey et al 2006;Maaroufi & Tanguay 2013). The importance of HSPs is not limited to heat stress management, but these molecules are also involved in other stresses, such as cold, osmoses, drought, salt, UV, high light, oxidative stress, and pathogen infection (Swindell et al 2007;Maaroufi & Tanguay 2013;Di Donato & Geisler 2019;Kumar et al 2020;Guo et al 2021).…”
Section: The Importance Of Hsps In Plant Protection During Droughtmentioning
confidence: 99%
“…However, plants have a limited "tool-box" with which they must generate adequate stress responses, and indeed, many reports have also demonstrated that central metabolic and signaling responses to different individual and combined stresses can share commonalities (Zhang and Sonnewald, 2017). In this context, of note are the Heat-Shock Protein (HSP) family, which were found in several cases to not only be important in heat stress, but to also be involved in plant immunity (Kumar et al, 2009;Park and Seo, 2015;di Donato and Geisler, 2019;Yu et al, 2016). HSPs are molecular chaperones responsible for protein folding, assembly, translocation, and degradation under both steady state and stress conditions.…”
Section: Introductionmentioning
confidence: 99%